Red clover silage improves milk fatty acid composition in dairy ewes - Guzatti G.C.* (2018)
© 2018, Agricultural Institute of Canada. All rights reserved.The purpose of this study was to evaluate the effects of two isoproteic total mixed rations containing either red clover (Trifolium pratense L.; RC diet) or lucerne (Medicago sativa L.; LU diet) silage as the major forage source on milk yield, milk composition, and milk fatty acid (FA) profile in dairy ewes. Sixteen dairy ewes were housed individually to receive the drawn diet (eight ewes eating each diet) and milked twice a day (0700 and 1500). Total dry matter intake, milk yield, milk composition, and nitrogen use efficiency were unaffected by treatments. The n-6/n-3 FA ratio tended to decrease, whereas the total polyunsaturated fatty acids (PUFAs) and PUFAs/ saturated fatty acids ratio increased in the milk fat of ewes fed the RC diet compared with ewes fed the LU diet. The presence of α-linolenic (C18:3n-3) and linoleic (C18:2n-6) acids in the milk fat was 22% higher in ewes fed the RC diet than in those fed the LU diet. Compared with the LU diet, the RC diet had no effect on milk yield and composition, but improved the milk FA profile in dairy ewes due to an increased proportion of PUFAs (in particular C18:3n-3 and, to a lesser extent, C18:2n-6) and a decreased n-6/n-3 FA ratio.